Development and evaluation of an Individualised Outcome Measure (IOM) for randomised controlled trials in mental health - Pesola, Francesca; Williams, Julie; Bird, Victoria; Freidl, Marion; Le Boutillier, Clair; Leamy, Mary; Macpherson, Rob; Slade, Mike (Wiley, 2015)
Predefined, researcher-selected outcomes are routinely used as the clinical end-point in randomised controlled trials (RCTs); however, individualised approaches may be an effective way to assess outcome in mental health research. The present study describes the development and evaluation of the Individualised Outcome Measure (IOM), which is a patient-specific outcome measure to be used for RCTs of complex interventions. IOM was developed using a narrative review, expert consultation and piloting with mental health service users (n=20). The final version of IOM comprises two components: Goal Attainment (GA) and Personalised Primary Outcome (PPO). For GA, patients identify one relevant goal at baseline and rate its attainment at follow-up. For PPO, patients choose an outcome domain related to their goal from a predefined list at baseline, and complete a standardised questionnaire assessing the chosen outcome domain at baseline and follow-up. A feasibility study indicated that IOM had adequate completion (89%) and acceptability (96%) rates in a clinical sample (n=84). IOM was then evaluated in an RCT (ISRCTN02507940). GA and PPO components were associated with each other and with the trial primary outcome. The use of the PPO component of IOM as the primary outcome could be considered in future RCTs.